Bony labyrinth morphometry reveals hidden diversity in lungless salamanders (Family Plethodontidae): Structural correlates of ecology, development, and vision in the inner ear. (2nd September 2019) - Capshaw, Grace; Soares, Daphne; Carr, Catherine E.
Abstract: Lungless salamanders (Family Plethodontidae) form a highly speciose group that has undergone spectacular adaptive radiation to colonize a multitude of habitats. Substantial morphological variation in the otic region coupled with great ecological diversity within this clade make plethodontids an excellent model for exploring the ecomorphology of the amphibian ear. We examined the influence of habitat, development, and vision on inner ear morphology in 52 plethodontid species. We collected traditional and 3D geometric morphometric measurements to characterize variation in size and shape of the otic endocast and peripheral structures of the salamander ear. Phylogenetic comparative analyses demonstrate structural convergence in the inner ear across ecologically similar species. Species that dwell in spatially complex microhabitats exhibit robust, highly curved semicircular canals suggesting enhanced vestibular sense, whereas species with reduced visual systems demonstrate reduced canal curvature indicative of relaxed selection on the vestibulo‐ocular reflex. Cave specialists show parallel enlargement of auditory‐associated structures. The morphological correlates of ecology among diverse species reveal underlying evidence of habitat specialization in the inner ear and suggest that there exists physiological variation in the function of the salamander ear even in the apparent absence of selective pressures on the auditory system to support acoustic behavior.